2004
DOI: 10.1073/pnas.0305627101
|View full text |Cite
|
Sign up to set email alerts
|

Stable association between strains of Mycobacterium tuberculosis and their human host populations

Abstract: Mycobacterium tuberculosis is an important human pathogen in virtually every part of the world. Here we investigate whether distinct strains of M. tuberculosis infect different human populations and whether associations between host and pathogen populations are stable despite global traffic and the convergence of diverse strains of the pathogen in cosmopolitan urban centers. The recent global movement and transmission history of 100 M. tuberculosis isolates was inferred from a molecular epidemiologic study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
324
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(355 citation statements)
references
References 47 publications
26
324
3
2
Order By: Relevance
“…Moreover, consanguinity and endogamy, which can reach 50 % in certain Tunisian areas (Ben Arab et al, 2004;Riou et al, 1989), may have contributed to the accommodation of particular M. tuberculosis genotypes. Overall, the findings are A. Namouchi and others in line with recent studies which revealed that certain mycobacterial lineages have adapted to specific human populations (Gagneux et al, 2006;Hirsh et al, 2004).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, consanguinity and endogamy, which can reach 50 % in certain Tunisian areas (Ben Arab et al, 2004;Riou et al, 1989), may have contributed to the accommodation of particular M. tuberculosis genotypes. Overall, the findings are A. Namouchi and others in line with recent studies which revealed that certain mycobacterial lineages have adapted to specific human populations (Gagneux et al, 2006;Hirsh et al, 2004).…”
Section: Discussionsupporting
confidence: 78%
“…The IS6110-based restriction fragment length polymorphism (IS6110-RFLP) (Van Soolingen et al, 1993), PCR-based spoligotyping (Kamerbeek et al, 1997) and mycobacterial interspersed repetitive units-variable number of tandem repeats (MIRU-VNTR) (Supply et al, 2000) typing methods have been, and are still, the most used. Combined with the recently developed whole genome-based typing approaches, a detailed picture of the global molecular epidemiology of TB has been obtained, revealing a geographically structured population of Mycobacterium tuberculosis with evidence for its adaptation to specific human populations (Brudey et al, 2006;Filliol et al, 2003Filliol et al, , 2006Gagneux et al, 2006;Gutacker et al, 2006;Hirsh et al, 2004;Sola et al, 2001). The factors contributing to the adaptability of M. tuberculosis strains or lineages to a particular population are poorly understood and several may be involved.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, populations of MTBC have been found to be highly geographically structured. In fact, previous studies shown a strong agreement between the geographical origin of a human host and the MTBC strain carried (Hirsh et al, 2004). In this work we analyzed MTBC samples collected from patients from Portugal and Northeast of Brazil.…”
Section: Introductionmentioning
confidence: 94%
“…Molecular studies suggest a long-standing coexistence of our species with bacterial organisms of the Mycobacterium tuberculosis complex (MTBC), although estimates for the coalescence of the MTBC lineages vary in an order of magnitude from thousands to tens of thousands of years (Brosch et al, 2002;Hirsh et al, 2004;Hershberg et al, 2008;Wirth et al, 2008;Comas et al, 2013;Bos et al, 2014). It is mainly the human and bovine forms that affect humans, which are transmitted via the respiratory and gastrointestinal routes, respectively (O'Reilly and Daborn, 1995).…”
Section: Introductionmentioning
confidence: 99%